Monitoring the impact of the COVID-19 lockdown on air quality in Lanzhou: Implications for future control strategies - Liu, Hui; Yu, Ye; Ma, Xiaoyi; Liu, Xinying; Dong, Longxiang; Xia, Dunsheng (Frontiers in Earth Science, 2023)
China implemented a one-month lockdown after the 2020 Spring Festival to prevent the spread of COVID-19. The closure measures provide a rare opportunity to understand the resulting changes in air pollution levels and to test the effectiveness of previous environmental protection measures. We used the time series decomposition method to quantify the air pollution in Lanzhou during the closure period. The results showed that during the epidemic lockdown period, although the concentration of SO2 in Lanzhou decreased substantially, there was a significant increase in the concentration of O3 (by 19.14%), followed by a gradual return to the normal level. Most of the changes during the COVID-19 lockdown were within the range of fluctuations over the past five years. The trend of decreasing SO2 and CO in 2020 was less than that during 2015–2019, and the continuous decline of the PM10 concentration exceeded expectations. NO2, PM2.5 and O3 maintained the trend of the previous five years. Our results show that temporary social closure measures have a limited effect on improving air quality in Lanzhou, and they emphasize the importance of reducing the O3 concentration in the future.